2004
DOI: 10.1098/rsbl.2004.0189
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone transgenic salmon pay for growth potential with increased predation mortality

Abstract: Recent advances in gene technology have been applied to create fast-growing transgenic fish, which are of great commercial interest owing to their potential to shorten production cycles and increase food production. However, there is growing concern and speculation over the impact that escaped growth hormone (GH)-transgenic fish may have on the natural environment. To predict these risks it is crucial to obtain empirical data on the relative fitness of transgenic and non-transgenic fish under nature-like condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
95
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(106 citation statements)
references
References 21 publications
9
95
1
1
Order By: Relevance
“…Yet it remains a controversial technique, both in terms of its consequences for wild populations, and with respect to its ability to successfully increase fish biomass (Nordeide et al 1994;Olla et al 1998;Salvanes 2001;Myers et al 2004). The effects of the relaxed selection pressures in hatcheries and the release of fishes with divergent genetic backgrounds have played a central role in the debate, with fears for the consequences of the likely hybridization between released and wild fishes McGinnity et al 1997McGinnity et al , 2003Myers et al 2004;Sundstrøm et al 2004). Other concerns focus on the altered behaviour of hatchery fishes.…”
Section: Introductionmentioning
confidence: 99%
“…Yet it remains a controversial technique, both in terms of its consequences for wild populations, and with respect to its ability to successfully increase fish biomass (Nordeide et al 1994;Olla et al 1998;Salvanes 2001;Myers et al 2004). The effects of the relaxed selection pressures in hatcheries and the release of fishes with divergent genetic backgrounds have played a central role in the debate, with fears for the consequences of the likely hybridization between released and wild fishes McGinnity et al 1997McGinnity et al , 2003Myers et al 2004;Sundstrøm et al 2004). Other concerns focus on the altered behaviour of hatchery fishes.…”
Section: Introductionmentioning
confidence: 99%
“…This concern has led to numerous articles on the conceptual problem of ecological risk-assessment (8)(9)(10), and several laboratory and theoretical studies have addressed the fitness and/or ecological consequences of transgenic animals (11)(12)(13)(14)(15)(16)(17). However, except for a few field trials on nematodes and mites, few empirical studies to evaluate the direct ecological effects of transgenic animals in more natural environments have been undertaken (18,19).…”
mentioning
confidence: 99%
“…The rate of development in the early life history of salmonids has important implications for fitness with respect to emergence timing and optimal conditions for foraging, predator avoidance, and migration (Einum and Fleming 2000;Sundstrom et al 2004Sundstrom et al , 2005. Salmonid fishes suffer severe mortality when they emerge from the gravel nests in which they are fertilized (Elliot 1989).…”
mentioning
confidence: 99%
“…Emergence timing is also influenced by spawning date in salmonids, but embryonic 1 development rate, thought to be adapted to local thermal environments (Tallman 1986;Beacham 1988;Hebert et al 1998), also has significant effects on emergence size and timing. Fish that hatch earlier have a size advantage over fish that hatch later (Mason and Chapman 1965), but timing of emergence must be carefully balanced with conditions for food availability (Sundstrom et al 2004(Sundstrom et al , 2005. In addition to correlation of development rate and early life history traits, investigators have observed a correlation among faster development rate, growth, and age at sexual maturity (Allendorf et al 1983).…”
mentioning
confidence: 99%